2005
DOI: 10.1158/1535-7163.mct-05-0010
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally replicative adenovirus expressing degradation-resistant p53 for enhanced oncolysis of human cancer cells overexpressing murine double minute 2

Abstract: Conditionally replicative adenoviruses (CRAd) are under investigation as anticancer agents. Previously, we found that the CRAd Ad#24-p53, expressing the p53 tumor suppressor protein from its genome, more effectively killed most human cancer cells than did its parent Ad#24. However, a minority of cancer cell lines poorly responded to the oncolysis-enhancing effect of p53. Here we show that refractory cell lines expressed high levels of the major negative p53 regulator murine double minute 2 (MDM2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Strategies for temporarily blocking the function of reticuloendothelial cells and hepatic uptake during intravascular administration of vectors have been reported already by the laboratories of Seymour [51][52] and Gerritsen, 53 respectively. These include: bisphosphonates and Gadolinium to inhibit the function of the reticulendothelial cells, reactive polymers to cover the charges of the adenoviral vector, [51][52] and mutational change of the adenoviral vector fiber protein and the penton base proteins, to decrease uptake into the hepatocytes.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies for temporarily blocking the function of reticuloendothelial cells and hepatic uptake during intravascular administration of vectors have been reported already by the laboratories of Seymour [51][52] and Gerritsen, 53 respectively. These include: bisphosphonates and Gadolinium to inhibit the function of the reticulendothelial cells, reactive polymers to cover the charges of the adenoviral vector, [51][52] and mutational change of the adenoviral vector fiber protein and the penton base proteins, to decrease uptake into the hepatocytes.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…These include: bisphosphonates and Gadolinium to inhibit the function of the reticulendothelial cells, reactive polymers to cover the charges of the adenoviral vector, [51][52] and mutational change of the adenoviral vector fiber protein and the penton base proteins, to decrease uptake into the hepatocytes. 53 …”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…Importantly, we found previously that exogenous p53 expression enhanced the cancer cell killing potency of an oncolytic adenovirus (17). Recently, however, we found that high expression of MDM2 limited the anticancer effect of exogenous p53 expressed by oncolytic adenoviruses (18).…”
Section: Introductionmentioning
confidence: 83%
“…Paradoxically, enhanced p53 expression increased the oncolytic potency of CRAds in the presence of E1B-55kD (30,31). The dilemma can be explained by two phenomena.…”
Section: Discussionmentioning
confidence: 99%